THE ROLE OF THE THERAPIST IN THE EARLY DIAGNOSIS OF RHEUMATOID ARTHRITIS - Mirzohid S. Musakov; Alibek A. Xudoynazarov; Lyubov A. Rempel (Web of Journals Publishing, 2025)
Rheumatoid arthritis (RA) is a chronic inflammatory disease of the joints of unknown etiology, which has a varied clinical course and is characterized by progressive destruction of synovial joints, accompanied by degradation of cartilage and bone, with possible spread outside the musculoskeletal system. The peak onset of rheumatoid arthritis occurs between 45 and 65 years of age. Women are susceptible to this disease 2-3 times more often than men. Rheumatoid arthritis continues to be one of the most pressing pathologies in modern medical practice: on the one hand, this is facilitated by the prevalence of the disease - up to 2% in the general population; on the other hand, the high social and economic significance of the process, based on high rates of permanent disability in patients and the significant cost of treatment and necessary laboratory monitoring.
Keywords: Early rheumatoid arthritis, rheumatoid factor, diagnostic criteria.